PEMILIHAN MODA ANGKUTAN PENUMPANG PERKOTAAN BERBASIS AKTIVITAS - Budiarto, Arif; Sjafruddin, Ade (Jurnal Transportasi, 2007)
Abstract Traveling decision was part of activity scheduling process which to be basis of activity demand modeling. In activity-based modeling, traveling was defined as movement with sequential process concentrating to through segments starting from home and back to home which more realistic than old model, trip based which used by four stages model. Using this approach model, the transport passenger modal split which was usually done by the people are analyzed in order to answer why recently the use of motorcycle was increased in number. The proportion of motorcycle which was increased in composition of roadway traffic reflect to the condition of modal split which done by the people from the available mode. Modal split was conditional decision on choosing decision in previous level, i.e. pattern of acitivity, time of the day, destintion and number of stop. The results of this study was expected to provide detail description of variables which were very influence to transportation modal split process.Keywords: mode choice, activity-based